Analysis of factors influencing the burden on family caregivers of disabled older adults in Guangzhou - Lin, Danrong; Liao, Junbin; Liu, Yanxi; Zhong, Yuquan; Pan, Jingyun; Fang, Heng; Lin, Yunfeng; Yao, Yilu; Su, Jiewen; Hu, Bingjie; Zhu, Wei (Frontiers in Public Health, 2025)
ObjectiveThis study aims to investigate the current status of disability among older adults and analyze factors influencing the burden on their family caregivers in southern China.MethodsA cross-sectional survey was conducted among 334 pairs of disabled older adults (≥65 years) and their primary family caregivers across three districts in Guangzhou. Face-to-face interviews using standardized questionnaires assessed disability levels via the “Long-term Care Disability Level Assessment” scale and caregiver burden via the Zarit Burden Interview (ZBI) scale. For ordinal variables, the Kruskal-Wallis H test was applied for multi-group comparisons, while the Mann–Whitney U test was used for two-group analyses. Statistical significance was set at p < 0.05. Ordinal logistic regression identified factors associated with caregiver burden.ResultsAmong 334 disabled older adults in Guangzhou, the mean age was 82 years. Of these, 55.7% were married, 43.4% were male, 43.4% had an educational attainment of primary school or below. For the 334 family caregivers, 62.3% were female, 36.8% had completed high school or vocational education. The median years of caregiving experience was 5 years, with a median weekly caregiving time of 70 h. Caregiver burden distribution was as follows: 16.2% no burden, 41.0% mild burden, 28.7% moderate burden, and 14.1% severe burden. Statistically significant differences in caregiver burden were observed across the following variables (p < 0.05): disabled old adults’ activities of daily living (ADL), caregivers’ gender, child in school, physical disease, years of caregiving experience, weekly caregiving time, social interaction frequency, life satisfaction, and social support network size. Higher caregiver life satisfaction and elevated ADL scores in care recipients emerged as protective factors. Conversely, longer weekly caregiving hours and caregivers’ physical illness were identified as risk factors.ConclusionThis study identifies weekly caregiving time, caregivers’ physical disease, disabled older adults’ ADL capacity, and caregivers’ life satisfaction as critical determinants of burden severity in aging China, advocating multilevel interventions.